Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.

A Guide to Participatory Outcome-Focused Monitoring with Most Significant Change, Outcome Harvesting, and Outcome Mapping - Smith, Richard (CARE, 2023)
Audience This guidance is primarily aimed at development and humanitarian professionals who design or manage monitoring and evaluation processes to support design and implementation of qualitative monitoring using Most Significant Change (MSC), Outcome Harvesting (OH), or Outcome Mapping (OM), which are participatory, outcome-focused qualitative methods. Purpose This guidance is a resource to strengthen qualitative monitoring, specifically addressing commonplace gaps or weakness in the monitoring of complex development and humanitarian projects. Importantly, these gaps include: 1. Lack of evidence about unexpected, as well as expected, changes or outcomes, especially during project implementation. 2. Limited documentation about whether and how a project contributed to change. Such information is vital to learning about what worked and how to build on successes. 3. Limited data to inform the review of theories of change, which limits their function and relevance. Addressing these monitoring gaps has the potential to contribute to more informed and effective adaptive management and learning. This guidance can be used to support the design and implementation of monitoring exercises using MSC, OH, and OM. Specifically, it supports users in choosing among MSC, OH, and OM or blending elements from these approaches. Additionally, it provides practical tips and examples - including expertise gained during the two pilot qualitative monitoring activities conducted in Niger and Bangladesh - as well as other publicly available materials. 1. Relevant CARE guidance and tools include: 1. Qualitative Methods Guidance Note for Monitoring, Evaluation and Learning (MEL) at CARE; 2. Outcome Mapping Manual: Development of a monitoring system for the Right to Food project using Outcome Mapping, CARE Nepal; 3. Tipping Point MEL Methods Brief: Outcome Mapping; 4. The Rolling Profile Tool.